El Modelo de Enseñanza y Aprendizaje de la Licenciatura en Enfermería de la Universidad de Costa Rica: una reflexión. - Ligia Murillo Castro (Universidad de Costa Rica, 2012)
This paper presents the model of teaching nursing career from his emergence as a discipline, something that was consolidated in the area of Costa Rica to establish as a career at the University of Costa Rica. First there will be a reflection on the socio-historical and professional context of nursing, later lectures on epistemological issues, the engines of the curriculum of the Bachelor of Nursing who teaches at the University of Costa Rica, and concludes with some important elements to consider regarding the position and implementation of educational courses and nursing intervention modules.